(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
Stroke is the third most common cause of death in developed country after cancer & ischemic heart disease. It is also one of the leading causes of death in developing countries like Bangladesh. Several studies have been done on stroke. But the difference between ischemic and hemorrhagic stroke on the basis of serum C-reactive protein (CRP) level has not been yet studied in Bangladesh. The aim of the study was to evaluate the differentiating role of CRP level between ischemic & hemorrhagic stroke patient in Bangladeshi population. A cross sectional prospective study was performed on 50-stroke patients in Bangabandhu Sheikh Mujib Medical University from January 2006 to December 2007. The study subjects were divided into ischemic & hemorrhagic groups on the basis of CT scan report. Serum CRP & Lipid profile was determined by standard method. Statistical analysis was performed by using SPSS software. Mann whitney. U test was done to see the level of significance. The study showed that mean serum CRP level was 9.69 mg/L that was higher than normal subjects & serum CRP level is 3.25 mg/L in ischemic & 13.05 mg/L in hemorrhagic stroke patient. The present study showed that serum CRP level is higher in hemorrhagic stroke than ischemic stroke. The study revealed that serum CRP level is a differentiator between ischemic and hemorrhagic stroke patients & helps the physician to take necessary management plan. J. Dhaka National Med. Coll. Hos. 2013; 19 (01): 39-42